Hubungan peer group support, uang saku dan pola konsumsi pangan dengan status gizi lebih pada remaja - Julia Rahman; Iin Fatmawati; Muh. Nur Hasan Syah; Dian Luthfiana Sufyan (Jurusan Gizi Politeknik Kesehatan Kemenkes Aceh, 2021)
The problem of overweight in adolescents is caused by multiplicity, including friendships and also the amount of pocket money which will affect the pattern of daily food consumption. The purpose of this study was to analyze the relationship peer group support, pocket money, and food consumption patterns with overweight. This research is observational with a cross-sectional approach. The sample was selected by 50 respondents with stratified random sampling technique, this study was conduction in 2020. Data collected by interviews for respondent characteristics, peer group support, pocket money, and food consumption patterns using the Food Frequency Questionnaire (FFQ). Data analysis using Chi-Square Test. The results showed that there was a significant relationship between peer group support and overweight (p= 0,048), There is a significant relationship between pocket money and overnutrition (p= 0,001) and there is a significant relationship between food consumption patterns with overnutrition (p= 0,000). The results of the study indicated that there was a relationship between peer group support, pocket money, and food consumption patterns with overweight. From these results, it is hoped that adolescents will be able to minimize the influence of their peers and be able to allocate pocket money to consume nutritious daily food.